2017
DOI: 10.17756/jfcn.2017-043
|View full text |Cite
|
Sign up to set email alerts
|

Lutein and β-Carotene in Selected Asian Leafy Vegetables

Abstract: Carotenoids, such as lutein and β-carotene are generally recognized as antioxidants. However, only β-carotene has the pro-vitamin A activity. This study determined lutein and β-carotene in Asian leafy vegetables using reversed-phase high pressure liquid chromatography (HPLC). The selected samples were Chinese mustard (Brassica juncea var. rugose), water spinach (Ipomoea aquatic), Chinese spinach (Amaranthus tricolor), coriander (Coriandrum sativum), Chinese flowering cabbage (Brassica parachinensis), Chinese b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Many researchers have stated that vegetables and fruits are a source of carotenoids. Chandra-Hioe et al (2017) studied some vegetables in order to determine the range of β-carotene and found that the amount of β-carotene ranged from 1974 to 6604 μg/100 g. Hanson et al (2011) showed that the carotenoids contents varied depended on cultivar, stage of maturity, analysed part of the plants, environmental conditions, treatments of preharvest and postharvest, storage conditions and time and also seasonally. For example, flowering cabbage collected in dry season had higher βcarotene (96000 μg/100 g) than those harvested in wet season.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have stated that vegetables and fruits are a source of carotenoids. Chandra-Hioe et al (2017) studied some vegetables in order to determine the range of β-carotene and found that the amount of β-carotene ranged from 1974 to 6604 μg/100 g. Hanson et al (2011) showed that the carotenoids contents varied depended on cultivar, stage of maturity, analysed part of the plants, environmental conditions, treatments of preharvest and postharvest, storage conditions and time and also seasonally. For example, flowering cabbage collected in dry season had higher βcarotene (96000 μg/100 g) than those harvested in wet season.…”
Section: Resultsmentioning
confidence: 99%
“…Analytical methods described by Chandra‐Hioe et al . (2017) and Fanning et al . (2010) were used as the initial reference extraction methods.…”
Section: Methodsmentioning
confidence: 97%
“…e semi-FFQ was applied with a specific list of 44 high L/Z foods commonly consumed in the urban ai population, including eggs (chicken and duck) as an animal source, 33 vegetables, 6 legumes, 2 maize/corn products, and one nut. Lutein and zeaxanthin levels were estimated using data from the USDA [12] and studies conducted by arasena and Lawan [13], Chandra-Hioe et al [14], and Pasaporte et al [15]. ree nutritionists reviewed the semi-FFQ before starting the collection of L/Z intake.…”
Section: Methodsmentioning
confidence: 99%